PALANG SIGEMOY (Pangan Lokal Atasi Stunting Ciptakan Generasi Emas Tumbuh Optimal) - Padlilah, Rahmi; Ariyanti, Ririn (Borneo Community Health Service Journal, 2024)
Indonesia is currently facing nutritional problems with many incidents of stunting (short toddlers). Based on the Nutritional Status Monitoring (NSM) over the last three years, short toddlers have the highest prevalence compared to other nutritional problems such as malnutrition, thinness, and even obesity. Based on data from the BKKBN for the last 2 years, there were 3,066 babies experiencing malnutrition spread across five city districts in North Kalimantan and Malinau District, including City District where the stunting rate is quite high and Lubak Manis Village which is one of the stunting loci. Stunting causes children to grow unhealthy, their brain development is not optimal, and can cause mental disabilities. Therefore, efforts to overcome stunting can be done through improving nutrition for babies. One alternative solution to overcome this problem is by providing additional food made from local and protein. The aim of this community service is to utilize the potential of natural resources, namely tofu and Moringa leaves which are quite easy to obtain in the village. The targets of this community service activity are posyandu cadres and PKK mothers in Lubak Manis village. The method used in this community service is education on preventing stunting and processing tofu and Moringa leaves into Naget as additional food for children and toddlers (PALANG SIGEMOY). This community service was carried out for 2 days in May, namely on  May 15,16 2024. The place of this service activity was the Posyandu building in Lubak Manis village, Malinau Regency, North Kalimantan. The results of the activity were that the community was able to understand the benefits of food containing nutrients from tofu and Moringa leaves as additional food to overcome stunting and innovate the processing of tofu and Moringa leaves into delicious and nutritious nuggets as additional food ingredients for stunted babies and toddlers.